Estudo das propriedades óptico-eletrônicas de neurotransmissores - Araújo, Roniel de Lima (2022)
In this work, we will present a study of the structural, electronic, optical, vibrational and thermodynamic properties of the dopamine, l-dopa, noradrenaline and adrenaline crystals, through computer simulations in the DFT formalism (Density Functional Theory), where the generalized gradient approximation (GGA-PBE) and the hybrid functional HSE06 were used. From the experimental data of the four crystal structures, the optimization of the crystal geometry, calculation of the density of states and band structure, optical absorption, dielectric function, refractive index, optical conductivity, reflectivity, loss function, infrared and Raman spectrum and also Debye temperature, enthalpy, free energy, T*entropy and heat capacity were performed. The new lattice parameters found showed good agreement with the experimental values. Through the functional GGA-PBE (HSE06), we found that: dopamine presented an indirect band gap E = 3.8 eV (4.70 eV), for noradrenaline we obtained an indirect band gap E = 3.48 eV (4.40 eV), for adrenaline an indirect band gap E = 3.53eV (4.60 eV) and a direct band gap E = 3.09 eV (3.60 eV) was obtained for the l-dopa crystal. The analysis of the densities of electronic states made it possible to identify the contributions per atom to the states of the valence and conduction bands. In the optical properties, it is possible to observe an absorption of light in the ultraviolet region, and a greater sensitivity in the absorption of polarized radiation in the 100 direction, for dopamine, noradrenaline, and l-dopa, while adrenaline presents a greater absorption of polarized light with the polarization direction 001. IR and Raman spectra were calculated, and vibration modes analyzed. The thermal capacity at room temperature found was: 210.01 cal/cell.K, 121 cal/cell.K, 182 cal/cell.K and 103 cal/cell.K, for dopamine, l-dopa, noradrenaline and adrenaline, respectively.